2007
DOI: 10.1590/s0074-02762007005000041
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and level of antibodies to the circumsporozoite protein of human malaria parasites in five states of the Amazon region of Brazil

Abstract: The aim of this study was to determine the prevalence of malaria infection and antibodies against the repetitive epitopes of the circumsporozoite (CS) proteins of Plasmodium falciparum, P. malariae, P. vivax VK210, P. vivax VK247, and P. vivax-like in individuals living in the states of Rondônia, Pará, Mato Grosso, Amazonas, and Acre. Active malaria transmission was occurring in all studied sites, except in Acre. P. falciparum was the predominant species in Pará and Rondônia and P. vivax in Mato Grosso. Infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 20 publications
2
27
0
2
Order By: Relevance
“…In Brazil, the most frequent species that cause infection in humans are: P. vivax, which accounted for 83.7% of registered cases, P. falciparum, by 16.3% and P. malariae (rarely observed) 26 . However, studies conducted by ARRUDA et al 2 revealed a discrepancy between the prevalence of antibodies against P. malariae and the malaria cases officially reported. According to the authors, the low incidence of reports on this species is due to the thick smear method, the official technique for the diagnosis of malaria in Brazil, which does not allow the evaluation of morphological difference of erythrocytes infected with P. vivax and P. malariae, and this can lead to a misidentification of the species, underestimating the true incidence of the latter.…”
Section: Introductionmentioning
confidence: 93%
“…In Brazil, the most frequent species that cause infection in humans are: P. vivax, which accounted for 83.7% of registered cases, P. falciparum, by 16.3% and P. malariae (rarely observed) 26 . However, studies conducted by ARRUDA et al 2 revealed a discrepancy between the prevalence of antibodies against P. malariae and the malaria cases officially reported. According to the authors, the low incidence of reports on this species is due to the thick smear method, the official technique for the diagnosis of malaria in Brazil, which does not allow the evaluation of morphological difference of erythrocytes infected with P. vivax and P. malariae, and this can lead to a misidentification of the species, underestimating the true incidence of the latter.…”
Section: Introductionmentioning
confidence: 93%
“…In 2011, only 263,323 cases were reported [1]. In other Brazilian regions, the transmission risk is low or nonexistent [2]. In Mato Grosso, the disease is predominantly focal.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Já, a baixa frequência do P. malariae registrada nos sistemas de informação requer acompanhamento mais detalhado pelos diversos setores envolvidos no processo: estudos publicados relevam que a semelhança do P. malariae com o P. vivax pode provocar equívoco na identificação. O método de visualização adotado no Brasil, da microscopia da gota espessa de sangue, capaz de detectar densidades baixas de parasitos, 4 tem sido questionado por Arruda e colaboradores 24 em suas pesquisas na Amazônia Legal: esses autores destacaram uma diferença entre a prevalência de anticorpos contra P. malariae e os casos notificados oficialmente, e comentam que a técnica oficial, recomendada pelo Ministério da Saúde como padrão-ouro para detecção e identificação de parasitos da malária, não permite avaliar a diferença morfológica das hemáceas infectadas por P. vivax e P. malariae, podendo levar a uma identificação incerta da espécie e a um cálculo equivocado de incidência.…”
Section: Métodosunclassified